2020
DOI: 10.1080/00268976.2020.1776409
|View full text |Cite
|
Sign up to set email alerts
|

Descendant of the X-ogen carrier and a ‘mass of 69’: infrared action spectroscopic detection of HC 3 O + and HC 3 S +

Abstract: The carbon chain ions HC 3 O + and HC 3 S + -longer variants of the famous 'X-ogen' line carrier HCO + -have been observed for the first time using two cryogenic 22-pole ion trap apparatus (FELion, Coltrap) and two different light sources: the Free Electron Laser for Infrared eXperiments (FELIX), which was operated between 460 and 2500 cm −1 , and an optical parametric oscillator operating near 3200 cm −1 ; signals from both experiments were detected by infrared predissociation action spectroscopy. The majorit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 65 publications
(63 reference statements)
3
23
1
Order By: Relevance
“…The centrifugal distortion value, obtained in the same manner but at the MP2/cc-pVTZ level of theory, is 0.469 kHz, which is compatible with that obtained from the fit of the lines. The results of our calculations are in agreement with those obtained by Thorwirth et al (2020), which are also shown in Table 3. Finally, another potential candidate is HC 3 O − .…”
Section: Hc 3 N Hc 3 O +supporting
confidence: 91%
See 1 more Smart Citation
“…The centrifugal distortion value, obtained in the same manner but at the MP2/cc-pVTZ level of theory, is 0.469 kHz, which is compatible with that obtained from the fit of the lines. The results of our calculations are in agreement with those obtained by Thorwirth et al (2020), which are also shown in Table 3. Finally, another potential candidate is HC 3 O − .…”
Section: Hc 3 N Hc 3 O +supporting
confidence: 91%
“…The sulphur analogue HC 3 S + is a good candidate for detection given that C 3 S has a very high proton affinity (933 kJ mol −1 ) and is around five times more abundant than C 3 O. We searched for it in our line survey using the ab initio calculations of Thorwirth et al (2020) and derive an upper limit to its column density of 3 × 10 11 cm −2 , which implies an abundance ratio N(HC 3 S + )/N(C 3 S) < 0.04. The lower MH + /M ratio of C 3 S compared to C 3 O probably stems from the fact that routes to HC 3 O + involving O atoms can be efficient because of the high abundance of neutral O atoms, while the sulphur analogous routes would be less efficient because atomic sulphur is expected to be preferably in ionized rather than neutral form.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the centrifugal distortion value obtained using the same procedure at MP2/cc-pVTZ level of theory is compatible with that obtained from the fit of the lines. The computed dipole moment is 1.73 D. The results of our calculations are in agreement with those obtained by Thorwirth et al (2020), which were made using the same procedure but at a different level of theory.…”
Section: Quantum Chemical Calculations For Hc 3 S +supporting
confidence: 88%
“…From the derived rotational and distortion constants we conclude, based on detailed ab initio calculations, that the best possible carrier is HC 3 S + , the protonated form of C 3 S. We succeeded in producing this cation in the laboratory and measured its microwave spectrum, which fully confirms our assignment. Previous laboratory studies of this species were performed by Thorwirth et al (2020) who measured its vibrational spectrum through infrared observations at low spectral resolution. We present a detailed observational study of protonated S-bearing carbon chains in this cloud and discuss these results in the context of a state-of-the-art gasphase chemical model.…”
Section: Introductionmentioning
confidence: 99%
“…They identify and assign four lines in their spectra to the J = 6 → 5, J = 7 → 6, J = 8 → 7, and J = 9 → 8 transitions between 32.8-49.2 GHz. The initial assignment was based on quantum chemical calculations in the same paper, as well as from Thorwirth et al (2020). Laboratory spectroscopy presented in the same paper confirms the detection.…”
Section: Hc 3 S + (Protonated Tricarbon Monosulfide)mentioning
confidence: 82%